2004
DOI: 10.1038/ng1299
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic yet biased expression of multiple Dscam splice variants by individual cells

Abstract: The Drosophila melanogaster gene Dscam is essential for axon guidance and has 38,016 possible alternative splice forms. This diversity can potentially be used to distinguish cells. We analyzed the Dscam mRNA isoforms expressed by different cell types and individual cells. The choice of splice variants expressed is regulated both spatially and temporally. Different subtypes of photoreceptors express broad yet distinctive spectra of Dscam isoforms. Single-cell RT-PCR documented that individual cells express seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
223
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 24 publications
18
223
0
Order By: Relevance
“…Is this process highly regulated or does it occur in a random or stochastic manner? Microarray experiments have revealed little if any regulation of exon 6 splicing 11,27 , which is consistent with the biology of Dscam. In the nervous system, it seems that the actual identity of the Dscam isoforms that are expressed is unimportant, provided that each neuron expresses a different set of isoforms than the neighboring neurons 11,[28][29][30][31] .…”
supporting
confidence: 62%
“…Is this process highly regulated or does it occur in a random or stochastic manner? Microarray experiments have revealed little if any regulation of exon 6 splicing 11,27 , which is consistent with the biology of Dscam. In the nervous system, it seems that the actual identity of the Dscam isoforms that are expressed is unimportant, provided that each neuron expresses a different set of isoforms than the neighboring neurons 11,[28][29][30][31] .…”
supporting
confidence: 62%
“…The possibilities for alternative spli cing increase markedly when exons have undergone tandem duplication 132 , such as for the D. melanogaster Down's syndrome cell-adhesion molecule (Dscam) gene, which functions in complex neuronal processing by generating tens of thousands of protein variants from a single gene through differential RNA processing 132,133 . Both the complexity and expression patterns of Dscam isoforms in haemocytes indicate that Dscam might have a role in immune function 133,134 . Recent studies have defined differences in the expression of Dscam isoforms in haemocytes, fat cells and brain tissue 10 .…”
Section: Variation In Invertebrate Immune Receptorsmentioning
confidence: 99%
“…The immunoglobulin superfamily protein, Dscam1, was a good candidate for several reasons. First, the Dscam1 locus can generate tens of thousands of different recognition molecules through alternative splicing [5] and each neuron appears to express a unique combination of isoforms [6]. Second, each Dscam1 isoform mediates homophilic, but not heterophilic binding with other isoforms and thus, this single gene could generate the diversity required for self-recognition throughout the nervous system [7].…”
Section: Reviewmentioning
confidence: 99%
“…Although both of these scenarios would confer a discrete cell surface identity upon each neuron, the former scenario requires a complex alternative splicing mechanism, whereas the latter can be achieved through stochastic expression of many Dscam1 isoforms within each cell. Expression studies in mushroom body neurons (as well as several other subclasses) argue that many isoforms are expressed in each neuron and that the expression pattern is largely random [6]. In addition, genetic studies demonstrated that the type of isoform expressed in each MB neuron is not important; rather, what is crucial is that an individual MB neuron expresses different isoforms from its neighbors [9][10][11].…”
Section: Reviewmentioning
confidence: 99%